Case report: Neuronal intranuclear inclusion disease presenting with acute encephalopathy - Bu, Julia Ting; Torres, Dolores; Robinson, Adam; Malone, Corey; Vera, Juan Carlos; Daghighi, Shadi; Dunn-Pirio, Anastasie; Khoromi, Suzan; Nowell, Justin; Léger, Gabriel C.; Ciacci, Joseph D.; Goodwill, Vanessa S.; et al. (Frontiers in Neurology, 2023)
Neuronal intranuclear inclusion disease (NIID), a neurodegenerative disease previously thought to be rare, is increasingly recognized despite heterogenous clinical presentations. NIID is pathologically characterized by ubiquitin and p-62 positive intranuclear eosinophilic inclusions that affect multiple organ systems including the brain, skin, and other tissues. Although the diagnosis of NIID is challenging due to phenotypic heterogeneity, greater understanding of the clinical and imaging presentations can improve accurate and early diagnosis. Here we present 3 cases of pathologically-proven adult-onset NIID, all presenting with episodes of acute encephalopathy with protracted workups and lengthy time between symptom onset and diagnosis. Case 1 highlights challenges in the diagnosis of NIID when MRI does not reveal classic abnormalities and provides a striking example of hyperperfusion in the setting of acute encephalopathy, as well as unique pathology with neuronal central chromatolysis, which has not been previously described. Case 2 highlights the progression of MRI findings associated with multiple NIID-related encephalopathic episodes over an extended time period, as well as the utility of skin biopsy for antemortem diagnosis.